Advancing Identity Theory: Examining the Relationship between Activated Identities and Behavior in Different Social Contexts. (September 2013) - Carter, Michael J.
This study advances identity theory by testing the impact of (moral) identity activation on behavior in different social contexts. At a large southwestern university, 343 undergraduate students completed a survey that measured meanings of their moral identity. Later they completed a laboratory task in which they were awarded more points than they deserved. Participants were given the opportunity to admit (or not admit) the improper point reward. Behavior during the task was examined in varying social contexts: when a participant's moral identity was activated (or not activated) and when participants completed the task while alone, in a group, or in a group where a numeric majority pressured them to not admit being given extra points. Results show that individuals behave in accord with identity meanings across social contexts when an identity is activated. Implications for identity theory regarding identity activation and how identities influence behavior across social contexts are discussed.